PENGARUH MODEL INKUIRI TERBIMBING BERBANTUAN MEDIA GOOGLE SITE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS - Quratu Aini, Salsabila; Asyiah, Nur; Huda, M.Khozinul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking skills are essential competencies that need to be developed in students to face the challenges of 21st-century learning, especially in IPAS subjects that require a deep understanding of concepts and reasoning. This research aims to determine the effect of the guided inquiry model assisted by Google Sites media on the critical thinking skills of fifth grade students with a sample of 15 students in IPAS subjects. The study employed a quantitative method with a pre-experimental design using a one-group pretest-posttest design. The data were collected using essay tests analyzed through normality test, N-Gain, and paired sample t-test. The results showed a significant increase in students' critical thinking skills. The average pretest score was 42,5, while the posttest average was 77,9. The N-Gain score was 0.6264 (moderate category), and the paired t-test revealed a significance value of 0.000 (< 0.05). These results indicate a significant effect of the guided inquiry model assisted by Google Sites media on students' critical thinking skills.